Electronic health record in military healthcare systems: A systematic review - Torab-Miandoab, Amir; Basiri, Mahdi; Dabbagh-Moghaddam, Arasb; Gholamhosseini, Leila (PLOS ONE, 2025)
Introduction The immediate access to detailed patient data is vital for effective medical care in military and emergency scenarios, enhancing diagnosis, treatment, and monitoring of military personnel. The integration of electronic health records (EHRs) is urgently needed in military healthcare systems, despite the distinct hurdles involved. Current literature on EHR use in military healthcare is lacking and disjointed. This study aims to bridge this gap through a systematic review, offering a thorough examination of the advantages, obstacles, and recommended strategies for implementing EHRs in military healthcare environments. Materials and methods According to the PRISMA guideline, a comprehensive electronic search of all relevant literature on the topic was carried out across multiple databases, including PubMed, Web of Science, Scopus, IEEE, ProQuest, MEDLINE, Cochrane Library, Embase, SID, and ISC up to July 20, 2024. The inclusion criteria involved choosing English-language articles that were available in full text and closely aligned with the study’s objectives. The data extraction sheet for each study included information including the authors, publication year, country, research goals, architecture and components, context, processes involved, standards utilized, platform and technology, level of implementation, interoperability issues, challenges faced, information resources, and significant findings. Results A total of 9,618 titles were retrieved from different databases. After removing duplicates, 6,051 titles were left. Upon evaluation, 29 articles were chosen for inclusion in the review. The results show that most of the studies were carried out at the United States Department of Defense (DoD) level with the aim of improving the quality of care and patient safety, as well as integrating healthcare delivery. Additionally, the studies covered various processes such as clinical documentation, appointment scheduling, research, telemedicine, decision support, and computerized physician order entry. Health level seven fast healthcare interoperability resources (HL7 FHIR), clinical document architecture (CDA), health insurance portability and accountability act (HIPAA), international classification of diseases 10th and 9th revision (ICD 10, ICD 9), international organization for standardization technical committees (ISO TC), software development kits (SDKs), and web-based architecture are some of the most important requirements for implementing EHR. The most significant challenges reported in the implementation of EHR included concerns about privacy and security, the sensitive military deployment environment, infrastructure limitations, and interoperability concerns. Conclusions Policymakers and practitioners can get insight from the findings regarding the standards that must be met, the challenges that must be overcome, and the requirements for EHR implementation in military healthcare settings. It could be a useful starting point when implementing EHRs in military healthcare systems, especially in nations where e-health development and planning are still in their early stages.